1967
DOI: 10.1084/jem.125.3.457
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Pinocytosis in Mouse Macrophages

Abstract: A prior publication described the pinocytosis-inducing properties of a variety of both high and low molecular weight molecules (1). This study indicated that anionic molecules stimulated the formation of pinocytic vesicles whereas neutral and cationic species had in most instances little influence on this parameter of endocytic activity. Some of the most potent inducers proved to be macroanions and these molecules were thought to function by virtue of a physicochemical interaction with a membrane receptor. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…The influence of exogenous nucleotides on macrophages was identified by Cohn and Parks which paved the way for further research into the involvement of extracellular purine and pyrimidine nucleotides during inflammation [67]. The authors showed adenine nucleotides to be implicated in the pinocytic vesicle formation in mouse macrophage cultures.…”
Section: Macrophagesmentioning
confidence: 99%
“…The influence of exogenous nucleotides on macrophages was identified by Cohn and Parks which paved the way for further research into the involvement of extracellular purine and pyrimidine nucleotides during inflammation [67]. The authors showed adenine nucleotides to be implicated in the pinocytic vesicle formation in mouse macrophage cultures.…”
Section: Macrophagesmentioning
confidence: 99%
“…91 In this study the authors showed that addition of adenine nucleotides to a mouse macrophage culture resulted in a dramatic increase in pinocytic vesicle formation. After this early study, exogenous nucleotides as a stimulant for macrophages were basically neglected for several years and resurrected only in 1985 by Silverstein and coworkers, 92 who reported that extracellular ATP inhibited Fc receptor-mediated phagocytosis and at the same time caused influx of Na ϩ , efflux of K ϩ , and an increase in [Ca ϩϩ ] i .…”
Section: Role Of P2 Receptors In Monocyte/macrophage Physiologymentioning
confidence: 99%
“…These include membrane current (43, 47, 63, 87, 118, 171, 227, 268, 332-335, 344, 380, 446, 484), increase in [Ca 2ϩ ] i (23,88,132,157,202,402,406), uptake of fluorescent dyes (65,168,184,185,202,402,427,438,444,446), membrane blebbing or other morphological change (80), spontaneous cell fusion (65,125), interleukin processing and release (43,129,130,155,158,366), activation of NF-B (131,133), killing of Mycobacterium tuberculosis (260,267,422), activation of p38 MAP kinase (186), activation of phospholipase D (111,112,200), formation of multinucleate giant cells (65,125), and various measures of cell death (see Ref. 100).…”
Section: Macrophages and Related Cellsmentioning
confidence: 99%